KORUPSI DAN KOLUSI PADA MASA RAFFLES - Machmoed Effendhie (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
In this article will be explained reasoning of sales policy appearance of private land during Raffles period. The focus of study is processing sale of private land in Java done by Raffles, starts from advertisement, auction, and individuals that is finally gets of best of private land. This simple article fully stems from gathering of archive or documen mustered by Dr. Rost is containing official letters, memorandum, petition, written testimony, minute, proceding, and others. Main conclusion from this article is sales policy of goverment land done by Raffles not pure as effort overcomes finance crisis, but also entangles interest of business of the functioners.